Tribological, mechanical and thermal response of diamond micro-particles reinforced copper matrix composites fabricated by powder metallurgy. (1st January 2023) - Poulose, Nixon; Selvakumar, P; Philip, Jibin T; George, Jees
Abstract: Copper/Diamond composites have gained a lot of attention in recent years due to their excellent thermal conductivity and their potential for use in high-power electronic devices. The current work targets on an experimental investigation of the tribological, mechanical, and thermal behaviour of copper diamond composite by using reinforced micro-diamond particles. Copper matrix composites with varying weight percentages of diamond particles were produced with the aid of the powder metallurgy. The wear tests were carried out on Pin-on-Disc wear test machine as per ASTM G99. The doping of an optimum amount of diamond particles (1% wt.) improved the overall wear performance by 51% under a normal load of 80 N. The doping had also showed a significant improvement in hardness by 26% and thermal conductivity by 1%. The primary wear mechanisms of Cu-Diamond composites appear to be a combination of brittle fracture, fragmentation of diamond-reinforced particles and ploughing in the Cu-alloy matrix.